1972
DOI: 10.1039/dt9720000604
|View full text |Cite
|
Sign up to set email alerts
|

27Al nuclear magnetic resonance studies of the hydrolysis and polymerisation of the hexa-aquo-aluminium(III) cation

Abstract: The hydrolysis of aluminium salt solutions has been studied using 27AI and 'H n.m.r. and this has led to reliable values for the concentrations of the species of AI(H,O)z+, A12(OH)2(H,0)~84+, and A11304(OH)24(H20),,7+ at different degrees of hydrolysis. These ions do not account for all the aluminium in solution and another species, probably A18(OH),,(H,0),4+ is thought to be present. It is shown that previous controversy over the constitution of these solutions arose because of the different methods used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(95 citation statements)
references
References 0 publications
4
89
0
1
Order By: Relevance
“…The ratio between the amounts of Al and OH -in the system has been found to be critical in the performance of the coagulant species (Strazdins 1986(Strazdins , 1989Öhman et al 1997). An especially stable and well-studied aluminum oligomer has the formula Al VI 12(H2O)24Al IV O4(H2O)12 7+ (Akitt et al 1972a;Bottero and Fiessinger 1989). Figure 11 represents the partial hydroxylation process by which trivalent aluminum ions, present in highly acidic aqueous solution, can be transformed to this advantageous species under suitable conditions of hydroxylation.…”
Section: Aluminum Sulfatementioning
confidence: 99%
See 1 more Smart Citation
“…The ratio between the amounts of Al and OH -in the system has been found to be critical in the performance of the coagulant species (Strazdins 1986(Strazdins , 1989Öhman et al 1997). An especially stable and well-studied aluminum oligomer has the formula Al VI 12(H2O)24Al IV O4(H2O)12 7+ (Akitt et al 1972a;Bottero and Fiessinger 1989). Figure 11 represents the partial hydroxylation process by which trivalent aluminum ions, present in highly acidic aqueous solution, can be transformed to this advantageous species under suitable conditions of hydroxylation.…”
Section: Aluminum Sulfatementioning
confidence: 99%
“…Moreover, unlike the use of alum or ferric chloride, there is no addition of chloride or sulfate ions to the water. Avoidance of sulfate ions can be important, both to avoid problems related to sulfate reducing bacteria (Roest et al 2005;Janssen et al 2009) and because sulfate ions have been shown to suppress the availability of coagulating species such as Al 3+ (Akitt et al 1972). There is also a possibility that by in-situ generation of the metal cations, within the medium that is being treated, the metal ionic species might be different initially from what can be achieved during addition of an inorganic coagulant.…”
mentioning
confidence: 99%
“…Many analytical methods have been used to characterize and quantify aluminum species. Traditional methods include potentiometric titration [4], Al-Ferron timed spectrophotometric assay [5,6] and 27 Al nuclear magnetic resonance ( 27 Al NMR) spectroscopy [7,8]. In addition, X-ray diffraction [9], Raman spectroscopy [10] and X-ray photoelectron spectroscopy [11] are used as aluminum speciation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the traditional ferron assay is much dependent on the cutoff time selected and the speciation resulting from this method is labile [8,11,12]. However, many studies [12][13][14] have concluded that Al b might be equitable to Al 13 , which can be confirmed by 27 Al NMR [14][15][16][17]. The inherent correlation between them remains vague since the kinetic models and analyses employed to describe the kinetic aluminum species reaction with ferron are various, and the derived rate constants are not regulated.…”
Section: Introductionmentioning
confidence: 89%